Entrance of the Matha in the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the principal entrance of the matha (monastic or residential building) of the Suhaveshwar Temple, facing north. At the centre of the façade, there is a protruding mukhamandapa (front porch) with a balcony above it. Both floors of the matha are semi-open. The north-facing wall has dwarf walls with pillars at regular intervals. The dwarf walls of the matha must have had kakshasanas (seat backs), but several of the slender seat backs are now lost.